(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This document explores the themes of hybridity and identity crisis in the works of Zadie Smith, a British author focusing on White Teeth, NW, and The Autograph Man. It leverages postcolonial theory, more specifically Homi K. Bhabha’s “third space” to analyze Smith’s characters and the multicultural contexts which shape their unevenly stitched patchwork identities. This paper emphasizes that hybridity in Smith’s works is not an ideal condition; rather, it is portrayed as emotionally charged and psychologically straining experience steeped in complex turmoil. Crises of identity illustrated through Irie Jones, Millat Iqbal, and Natalie Blake highlight the struggle of constructing a settled self amidst globalization and post-colonialism. Through her depiction of cultural hybridity Smith positions it as an area characterized by possibilities rather than seamlessly at ease which allows her to challenge essentialist perspectives while underpinning the apprehensions that accompany existence among cultures rising from differing eras, class structures or society frameworks. In conclusion, this work argues that through Smith’s fiction readers are encouraged to cultivate multifarious identities adaptable to our ever-fluid surroundings countering rigid criteria failing boundary markers.